GENERAL EDUCATION TEACHERS’ PERSPECTIVES ON CHALLENGES TO THE INCLUSION OF STUDENTS WITH INTELLECTUAL DISABILITIES IN QATAR - Alodat, Ali (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study examines the challenges that general education teachers face in implementing inclusive education for students with intellectual disabilities in Qatar. Employing a mixed-methods approach, quantitative data were collected from 255 teachers via a structured questionnaire, complemented by qualitative insights from semi-structured interviews with five participants. The findings indicate that teachers encounter moderate to high levels of difficulty, particularly in areas related to the school environment and the availability of educational resources. Significant demographic differences were observed, with male teachers and those working in primary schools reporting greater perceived barriers. Thematic analysis revealed six key factors influencing teachers’ perceptions: student diversity, instructional practices, teacher preparedness, school culture and environment, family and community involvement, and logistical challenges. Despite national policy support for inclusive education, the study reveals ongoing deficits in teacher training, institutional backing, and resource provision. These findings highlight the complex interplay of individual, institutional, and societal factors that shape inclusive education efforts. The study provides valuable insights for localizing inclusive education efforts in Qatar and similar contexts, with implications for educators, policymakers, and educational leaders who are committed to fostering equitable learning environments.